Perioperative Management of Patients Having Noncardiac Surgery Who Are Receiving Anticoagulant or Antiplatelet Therapy: An Evidence-Based but Practical Approach - Darvish-Kazem, Saeed; Douketis, James D. (Seminars in Thrombosis and Hemostasis, 2012)
Patients receiving anticoagulant or antiplatelet therapy who require noncardiac surgery represent a common yet challenging clinical problem. Clinicians must balance the risk of thromboembolic and major adverse cardiovascular events that are associated with interrupting these therapies, against the risk of bleeding from continuing these drugs in the perioperative period. Identifying patients at highest risk for such complications requires particular attention to the role of bridging therapy and the optimal timing and duration of drug withdrawal and resumption with surgery. Patients with coronary stents represent a population that requires specific considerations, due to the added risk and significant mortality associated with perioperative stent thrombosis. Minimizing this risk is dependent on several patient- and stent-specific factors. This review provides clinicians with a summary of the available evidence to facilitate a practical approach to the management of these patients while highlighting the need for continued research in this field.
Keywords: perioperative; antiplatelet; anticoagulant; noncardiac surgery; bridging anticoagulation